Web Accessibility: Designing User-Friendly Websites for Individuals with Visual Impairments - Maulana, Ihsan (Golden Ratio of Data in Summary, 2025)
Web accessibility is crucial to creating an inclusive digital space, particularly for individuals with disabilities. This study aims to analyze the application of Web Content Accessibility Guidelines (WCAG) principles on the Tokopedia e-commerce platform and to develop a prototype website that optimally integrates accessibility elements. The research employs a qualitative approach with a case study method, including website analysis, assistive technology testing using the NVDA screen reader, and prototype website development based on Tailwind CSS. The results reveal that Tokopedia has implemented some accessibility elements, such as heading structures and alt text, but still has shortcomings in keyboard navigation, ARIA attributes, and product descriptions. The prototype website successfully addresses these issues by providing optimized keyboard navigation, comprehensive use of ARIA attributes, and informative product descriptions. Testing shows that the prototype website is not only accessible to visually impaired users but also enhances usability for the general audience. This study concludes that web accessibility can improve inclusivity and user comfort for all. The findings provide practical guidance for web developers to optimize accessibility design and create a more equitable digital experience. Therefore, this research contributes to the literature and web accessibility practices in Indonesia.